2016
DOI: 10.4236/health.2016.81003
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorder in University Students of the <i>Parque das Rosas Campus, Universidade Estácio de Sá</i> That Practice Sports

Abstract: The stomatognathic system (SS) is a functional unit of the body that depends on the balance of several tissues. It consists of various structures, including the temporomandibular joint. Temporomandibular disorder (TMD) can occur due to alterations in the SS. The Fonseca Anamnestic Index (FAI) is a scale used to evaluate and to characterize the TMD Type: no DTM, mild, moderate and severe. The aim is to evaluate the prevalence of signs and symptoms related to TMD in university students of the Parque das Rosas Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several studies have investigated the gender differences in TMD prevalence and severity. In a survey conducted by Cabral et al, it was observed that signs and symptoms related to TMD were more prevalent among females than males [ 21 ]. A study from Saudi Arabia using Fonesca’s index and Zung anxiety scale found that 62.8% of female participants had high levels of anxiety in relation to TMD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the gender differences in TMD prevalence and severity. In a survey conducted by Cabral et al, it was observed that signs and symptoms related to TMD were more prevalent among females than males [ 21 ]. A study from Saudi Arabia using Fonesca’s index and Zung anxiety scale found that 62.8% of female participants had high levels of anxiety in relation to TMD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 The presenting features of TMD includes pain in the pre-auricular area, TMJ or masticatory muscles, Journal of Nepalese Prosthodontic Society (JNPS) restriction,limitation or deviation in mandibular motions, clicking in the TMJ during mandibular movements and fatigue of the head and neck muscles which are not associated to any growth and development disorders, systemic diseases and trauma. [1][2][3][4][5] Multifactorial etiologies ofTMD include occlusal disharmony, oral habits, dysfunction of masticatory muscles and adjacent structures, emotional stress and extrinsic and intrinsic changes on TMJ structure. [1][2][3][4][5][9][10][11][12][13][14][15][16] Studies have shown a high prevalence (60-70%) of TMD in general populations showing at least one sign of the disorder in a lifetime but only 5% of them seek for the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Multifactorial etiologies ofTMD include occlusal disharmony, oral habits, dysfunction of masticatory muscles and adjacent structures, emotional stress and extrinsic and intrinsic changes on TMJ structure. [1][2][3][4][5][9][10][11][12][13][14][15][16] Studies have shown a high prevalence (60-70%) of TMD in general populations showing at least one sign of the disorder in a lifetime but only 5% of them seek for the treatment. 1,5 Studies among the undergraduate university students have shown 40-70% prevalence of TMD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations